Assessing the Association between Anti-Diabetic Medication Adherence and Glycemic Control in Type 2 Diabetes - Aida Vatan Meidanshahi; Fariba Alaei-Shahmiri; Fatemeh Golgiri; Mohammad Ali Mavvaji; Bentolhoda Dinko; Raziyah Shahi; Sedighe Moradi (Iranian Journal of Diabetes and Obesity)
Objective: Adherence to anti-diabetic medications in diabetic patients plays a considerable role in glycemic control, prevention of short-term and long-term morbidities, and diabetes-related mortality. The current study aims to evaluate the factors associated with adherence to medications among patients with type 2 diabetes. Materials and Methods: The current study was conducted on 366 diabetic patients who were referred to the Institute of Endocrinology and Metabolism. The HbA1C was measured at baseline and then after six months. The validated questionnaire on adherence to refills and medication scale (ARMS) was filled, and factors associated with medication adherence were assessed. The higher ARMS scores represented poorer adherence to the medication. Results: Diabetic patients with adherence to anti-diabetic agents represented significantly lower levels of HbA1C both at baseline (P< 0.001) and the six-month follow-up (P< 0.001) compared to the non-adherent group. In the correlation analyses, the ARMS score was significantly correlated with the A1C levels measured at the baseline (rs= 0.37, P< 0.001) and after 6 months (rs= 0.40, P< 0.001) as well as the duration of diabetes (rs= 0.16, P= 0.003). The subsequent logistic regression analysis highlighted the use of insulin as the main determinant of adherence to medications (OR: 0.59; 95%CI: 0.35-0.99), after controlling for age, gender, diabetes duration and number of medications. Conclusion: The current study revealed that adherence to the anti-diabetic medication is associated with remarkably improved glycemic control. Diabetes duration and insulin use were inversely correlated with adherence to medication, while there was no association with age, gender, numbers of drugs.